HYDROFRACTURING OF THE FORM WITH THE INSTALLATION OF A GRAVEL FILTER - Tokar, Oleksandr Anatoliyovych; Korovyaka, E.A. (НТУ "Дніпровська політехніка", 2024)
Hydraulic fracturing is a crucial stage in modern oil and gas production, providing increased productivity of wells and optimization of the natural resource extraction process. This technological process allows to increase the permeability of the layer, which in turn increases the amount of extracted oil and gas. Hydraulic fracturing makes it possible to achieve effective removal of valuable resources from deep rock formations where they are located in difficult conditions [1]. One of the key advantages of hydraulic fracturing is the possibility of increasing the productivity of wells, which allows more efficient use of oil and gas deposits. This process also helps to increase the yield of oil and gas, which is critical for meeting the energy needs of modern society. In addition, hydraulic fracturing allows to reduce production costs and increase the efficiency of using natural resources [2, 3].